2019
DOI: 10.1111/lcrp.12152
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging interviewees to say more and deception: The ghostwriter method

Abstract: Background We examined a new method to encourage interviewees to say more, the ghostwriter method, and examined its effect on eliciting information and cues to deceit. Method A total of 150 truth tellers and liars either told the truth about a trip they made in the last 12 months or pretended to have made such a trip. They were allocated to a Control condition, a ‘Be detailed’ condition in which they were encouraged to report even small details and a ghostwriter condition in which they were told to imagine tal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 36 publications
3
44
0
Order By: Relevance
“…Complications and the proportion of complications yielded stronger results than common knowledge details and selfhandicapping strategies, which replicated the previous findings when these three variables were observed (Leal, Vrij, Deeb, & Kamermans, 2019;Vrij, Leal et al, 2017;Vrij, Leal, Jupe et al, 2018;. Unlike previous research, the proportion of complications did not yield a stronger effect than the total details variable Vrij, Leal et al, 2017;Vrij, Leal, Jupe et al, 2018;.…”
Section: Discussionsupporting
confidence: 79%
“…Complications and the proportion of complications yielded stronger results than common knowledge details and selfhandicapping strategies, which replicated the previous findings when these three variables were observed (Leal, Vrij, Deeb, & Kamermans, 2019;Vrij, Leal et al, 2017;Vrij, Leal, Jupe et al, 2018;. Unlike previous research, the proportion of complications did not yield a stronger effect than the total details variable Vrij, Leal et al, 2017;Vrij, Leal, Jupe et al, 2018;.…”
Section: Discussionsupporting
confidence: 79%
“…Previous research has shown the proportion of complications to be a more diagnostic indicator of veracity than the total details variable (Leal et al, ; Vrij et al, , , b, ). The proportion of complications represents the proportion of truthfulness and is defined as: complications/(complications + common knowledge details + self‐handicapping strategies).…”
Section: Discussionmentioning
confidence: 97%
“…Common knowledge details refer to strongly invoked stereotypical information about events (e.g., “We went to the Louvre Museum in Paris where we saw the Mona Lisa”) (Vrij, Leal, Jupe, & Harvey, ). Truth tellers typically report more complications than liars, whereas liars typically report more common knowledge details and self‐handicapping strategies than truth tellers (Leal, Vrij, Deeb, & Kamermans, ; Vrij et al, , , b, , ). The research to date also showed that complications is the most diagnostic cue out of these three variables.…”
Section: Veracity and The Information Providedmentioning
confidence: 99%
“…We checked our datasets and found five in which we examined plausibility and two other verbal cues we thought may be related to it: total details and complications Leal et al 2015;. In two of these datasets (Leal et al, 2019; an additional cue was examined which we also thought to have potential in explaining plausibility: verifiable sources. DePaulo et al (2003) defined plausibility as "the degree to which the message seems plausible, likely, or believable" (p. 113).…”
Section: Article In Pressmentioning
confidence: 99%